Invasive treatment of selected psychiatric diseases - Basiaga, Bartosz; Bednarz, Krzysztof; Trojan, Sara; Leśniak, Marek; Kwieciński, Jakub; Miszuda, Sławomir; Błaszczyk, Agnieszka; Fussek-Styga, Urszula; Szwedkowicz, Agata; Heluszka, Jakub (Quality in Sport, 2023)
Mental disorders are a significant clinical problem due to the frequent ineffectiveness of their treatment. This is due to the not fully understood etiopathogenesis of these diseases. Often, the mechanism of action of a given therapy is not known and it is not clear why treatments that work in some patients may not produce any clinical improvement in others. The currently used pharmacotherapy and psychotherapy often turn out to be insufficient, which prompts the search for other methods of therapy, including neurosurgical methods. The currently carried out attempts at neurosurgical treatment of mental disorders differ greatly in terms of precision and surgical technique from the controversial procedures from the middle of the last century. Ablative methods and deep brain stimulation, which has been increasingly used in recent years,